Operational characteristics and determination of resistance for effective powering and propulsion of fishing boats of lower Perak River of Malaysia - Molla, Md. Abul Hossain; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Leman, Zulkiflle; Ismail, Md. Yusof (Universiti Putra Malaysia Press, 2002)
The case study of a resistance and propulsion characteristics of a typical small traditional fishing boats of lower Perak River of Malaysia is reported in this paper. The aim of this study is to provide a better or more efficient method of determining the effective powering and propulsion of fishing boats. For the estimation of propeller characteristics, the propeller "SK" - series diagrams were used. The results of the calculations show that the efficiency of the conversion process of the engine power into the effective thrust can be improved by proper selection of the engine, propeller and its parameters. The power requirement of the engine according to the calculation was found to be 6.4 kW and 7.5 kW for the propeller speeds of 1000 rpm and 300 rpm respectively for Vs = 8.5 knots. Thus the power-displacement ratio varies from 1.28 kW/ton depending on the propeller speed. Efforts have been made for proper powering and propulsion of the traditional fishing boats in order to minimize the fuel cost.